2022
DOI: 10.3389/fcell.2022.894800
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Non-Coding RNAs in Familial Hypercholesterolemia, Theranostic Applications

Abstract: Familial hypercholesterolemia (FH) is a common monogenic disease which is associated with high serum levels of low-density lipoprotein cholesterol (LDL-C) and leads to atherosclerosis and cardiovascular disease (CVD). Early diagnosis and effective treatment strategy can significantly improve prognosis. Recently, non-coding RNAs (ncRNAs) have emerged as novel biomarkers for the diagnosis and innovative targets for therapeutics. Non-coding RNAs have essential roles in the regulation of LDL-C homeostasis, suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 183 publications
0
2
0
Order By: Relevance
“…It is regarded as one of the finest indicators for the electrochemical sensing method's early cancer diagnosis. 140 In 2020 Meng et al summarized and reported the enzymatic activities of MNCs and explored their applications in different fields, such as molecular diagnostics and pollution removal. 141 They placed particular emphasis on MNCs manufactured with protein as a protective agent.…”
Section: Reviewmentioning
confidence: 99%
“…It is regarded as one of the finest indicators for the electrochemical sensing method's early cancer diagnosis. 140 In 2020 Meng et al summarized and reported the enzymatic activities of MNCs and explored their applications in different fields, such as molecular diagnostics and pollution removal. 141 They placed particular emphasis on MNCs manufactured with protein as a protective agent.…”
Section: Reviewmentioning
confidence: 99%
“…In addition to cerebral ischemia reperfusion (I/R) models [43,44], a large body of data from other experimental models including human data indicates the biomarker and protective effects of miR-30c against I/R damage [45][46][47][48][49][50]. Existing evidence suggests that miR-30c attenuates cardiovascular dysfunctions [51][52][53], hyperglycemia [54][55][56], obesity [57], atherosclerosis [58][59][60], dyslipidemia [17], and hepatic lipoprotein production [61,62], which constitute major risk factors in stroke and other neurological disorders. MiR-30c potentiates prosurvival anti-apoptotic pathways [63][64][65].…”
Section: Role Of Mir-30c In Neurological Disordersmentioning
confidence: 99%